Holothuria (Selenkothuria) carere, a new species of sea cucumber (Echinodermata: Holothuroidea) from the Mexican Pacific - Honey-Escandón, Magali; Solís-Marín, Francisco A.; Laguarda-Figueras, Alfredo (Zootaxa, 2011)
A new species of sea cucumber of the subgenus Selenkothuria Deichmann, 1958 is described. Holothuria (Selenkothuria) carere n. sp. was found in the Mexican Pacific, from intertidal to 6 m depth. The absences of ossicles in the body wall, as well as in the dorsal and ventral tube feet make this species unique among the species of this subgenus. Smooth straight rods with distal perforations and projections are present only in the dorsal and anal papillae, papillae at the base of the tentacles and in the tentacles. This species is distinctive within the subgenus. The shape of the ossicles shows some similarities with H. (S.) glaberrima Selenka, 1867.